2020
DOI: 10.1111/clr.34_13643
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment modality after tooth extraction on soft tissue dimensional changes: RCT

Abstract: Background: Clinical research related to dimensional change after tooth extraction has mainly focused on the biology of bone, while the effect of soft tissue healing on bone modelling and dimensional changes in post-extraction sites have received little attention. Aim/Hypothesis: To compare soft tissue dimensional changes and relative differences in soft and hard tissue volumes 4 months after single tooth extraction and 3 different treatment modalities: spontaneous healing (SH), alveolar ridge preservation (DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Barring hard tissue preservation, the application of ARP aims to optimize soft tissue quality and quantity during socket healing. Although some studies have reported that some ARP techniques and materials are capable of mitigating the extent of soft tissue dimensional changes postextraction, 144,183,185,186 keratinized mucosa width, mucosal thickness, and the external soft tissue contour are not significantly different between alveolar ridges healed with or without ARP 27,72,184 . This lack of difference has been attributed to a great extent to a soft tissue thickening in spontaneous healing sites, especially when the buccal osseous wall is thinner than 1 mm 53,72,184 .…”
Section: What Is the Impact Of Arp To The Peri‐implant Soft Tissue Ph...mentioning
confidence: 95%
See 4 more Smart Citations
“…Barring hard tissue preservation, the application of ARP aims to optimize soft tissue quality and quantity during socket healing. Although some studies have reported that some ARP techniques and materials are capable of mitigating the extent of soft tissue dimensional changes postextraction, 144,183,185,186 keratinized mucosa width, mucosal thickness, and the external soft tissue contour are not significantly different between alveolar ridges healed with or without ARP 27,72,184 . This lack of difference has been attributed to a great extent to a soft tissue thickening in spontaneous healing sites, especially when the buccal osseous wall is thinner than 1 mm 53,72,184 .…”
Section: What Is the Impact Of Arp To The Peri‐implant Soft Tissue Ph...mentioning
confidence: 95%
“…65,179,180 In a recent trial, 144 and various grafts were used. 49,115,180,181 In contrast to the studies that reported that socket seal utilizing a xenograft and a free gingival graft 182,183 was able to limit the postextraction external soft tissue contour shrinkage, no significant differences in soft tissue contour changes were reported when ARP with a nonresorbable d-PTFE membrane and an allograft, 72 a collagen membrane and a bovine xenograft, 184 a xenograft, and a free gingival graft or a porcine collagen matrix as socket seal 34 were compared with unassisted socket healing. The findings of a recent systematic review and network meta-analysis 185 concluded that hard and soft tissues behave differently after ARP as a response to the choice of the biomaterials used.…”
Section: What Is the Impac T Of Arp To The Peri -Impl Ant Sof T Tissu...mentioning
confidence: 97%
See 3 more Smart Citations